Emerging Concepts in Analysis and Applications of Hydrogels 2016
DOI: 10.5772/62900
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Tailoring the Properties of Hydrogels Using Spectroscopic Methods

Abstract: Hydrogels represent heterogeneous systems that consist of a large amount of water retained by a three-dimensional network. The hydrogel network is the result of assembly through physical interactions or chemical cross-linking of polymers or small molecules. The applications of hydrogels (water purification, tissue regeneration, therapeutic delivery, bio-detection or bio-imaging, etc.) depend on their physicochemical properties and structural features. Although electron microscopy and viscoelastic measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 110 publications
(168 reference statements)
0
10
0
Order By: Relevance
“…The hydrogel could be microscopically named as a "two phases" system composed by water and the fibers network. The presence of water will interfere in the FTIR spectra (Ionita, 2016). Also, the water organization is different close to the fibers and in the solvent pools, Fig.…”
Section: Properties Of Pure Organogels and Hydrogelsmentioning
confidence: 99%
“…The hydrogel could be microscopically named as a "two phases" system composed by water and the fibers network. The presence of water will interfere in the FTIR spectra (Ionita, 2016). Also, the water organization is different close to the fibers and in the solvent pools, Fig.…”
Section: Properties Of Pure Organogels and Hydrogelsmentioning
confidence: 99%
“…Significant changes were observed in the symmetric and antisymmetric COO – stretching bands (1400 and 1600 cm –1 ). The separation of the positions of these two peaks decreased from 200 to 190 cm –1 , implying the coordination of the cation with one of the oxygen atoms, whereas the other oxygen forms hydrogen bonds with other groups. Furthermore, the broad band of OH stretching in the 3100–3600 cm –1 frequency region is narrower in the sample with 10 mM Ca 2+ addition. This indicates that the OH oscillators are involved in the formation of an ordered structure of the polysaccharide chain.…”
mentioning
confidence: 97%
“…Among the latter, supramolecular gels represent a class of materials that nowadays attract the scientific interest due to their diverse applicability in fields like pharmacy, cosmetics, pollutant capture/removal and catalysis. 5,57,58 Although EPR spectroscopy is not currently exploited to a large extent in this field, it can provide reliable information on the assembly of low molecular weight gelators (LMWG), on the encapsulation or diffusion of spin-labelled molecules into and from gel networks, and can be used to monitor the formation of polymeric gels. Only few studies report supramolecular gel formation based on changes in spin probe dynamics revealed by EPR spectroscopy.…”
Section: Formation and Properties Of Gels Evidenced By Epr Spectroscopymentioning
confidence: 99%
“…Over the last 50 years, supramolecular assemblies have been investigated by electron paramagnetic resonance (EPR) spectroscopy methods aiming at structural, dynamic and thermodynamic information. [1][2][3][4][5][6] A large variety of systems resulted by molecular assembly through non-covalent interactions have been explored. For more than three decades, an interesting research topic regarded the dynamic characterisation of ionic and non-ionic surfactants 6 in connection with their application as template agents in the preparation of mesoporous materials like silica or alumina.…”
Section: Introduction *mentioning
confidence: 99%